Developing writing teachers : practical ways for teacher-writers to transform their classroom practice - Locke, Terry
The premise of Developing Writing Teachers is this: When teachers of writing identify as writers, it adds a special dimension to their writing pedagogy. Practical and accessible while drawing on a range of relevant research and theory, this text is distinguished by its dual focus-on teachers as writers and the teaching of writing. Part I addresses the question, What does it take for a teacher of writing to develop an identity as writer? Using case studies and teacher narratives, it guides readers to an understanding of the current status of writing as the 21st century unfolds, the role of expressive writing in developing a writing identity, the relationship of writing to genre and rhetoric, writing and professional identity, and writing as design. Part II focuses on pedagogical practice and helping writer-teachers develop a toolkit to take into their classrooms. Coverage includes building a community of writing practice; the nature of writing as process; the place of grammar; the role of information, communication and representational technologies; and how assessment, properly used, can help develop writing. Ideal for for pre-service and in-service courses on the teaching of writing, the Companion Website provides aadditional readings/documents; PowerPoint presentations; assessment resources; and lesson and unit plans and planning guides.